Bootstrapping $$ \mathcal{N} $$ = 4 super-Yang-Mills on the conformal manifold - Chester,SM; Dempsey,R; Pufu,SS (Journal of High Energy Physics, 2023)
A bstract We combine supersymmetric localization results with numerical bootstrap techniques to compute upper bounds on the low-lying CFT data of $$ \mathcal{N} $$ N = 4 super-Yang-Mills theory as a function of the complexified gauge coupling τ . In particular, from the stress tensor multiplet four-point function, we extract the scaling dimension of the lowest-lying unprotected scalar operator and its OPE coefficient. While our method can be applied in principle to any gauge group G , we focus on G = SU(2) and SU(3) for simplicity. At weak coupling, the upper bounds we find are very close to the corresponding four-loop results. We also give preliminary evidence that these upper bounds become small islands under reasonable assumptions.